The Pseudepigrapha in Current Research - Sheinfeld, Shayna (Religion compass, 2013)
The Pseudepigrapha is a collection of Jewish and Christian texts usually attributed to ideal figures from the past. The Pseudepigrapha generally date from the Second Temple and early Christian period, approximately 200 B.C.E. to 200 C.E. While the term itself derives from the Greek meaning ‘falsely attributed,’ the function of pseudepigraphic texts is more complex than what in modern society would simply be forgery. Pseudepigraphy itself was not uncommon in the ancient world, and its usage in Jewish and Christian circles should come as no surprise to those familiar with the Greek education system, where pseudonymous writing was a basic pedagogical practice. This article will discuss current research on pseudonymous attribution and its function for the author of a pseudepigraphic text, which assists the author in handling present situations by emulating circumstances and ideal figures from the past. In addition, determining the provenance—whether Jewish or Christian—of individual pseudepigrapha is highly problematic, as these texts were preserved and transmitted by Christians and may therefore have been redacted. The latest research discussing how one might determine the provenance of an individual pseudepigraphic text will be explored.